2017
DOI: 10.1523/jneurosci.1619-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

K+Channel Modulatory Subunits KChIP and DPP Participate in Kv4-Mediated Mechanical Pain Control

Abstract: The K ϩ channel pore-forming subunit Kv4.3 is expressed in a subset of nonpeptidergic nociceptors within the dorsal root ganglion (DRG), and knockdown of Kv4.3 selectively induces mechanical hypersensitivity, a major symptom of neuropathic pain. K ϩ channel modulatory subunits KChIP1, KChIP2, and DPP10 are coexpressed in Kv4.3 ϩ DRG neurons, but whether they participate in Kv4.3-mediated pain control is unknown. Here, we show the existence of a Kv4.3/KChIP1/KChIP2/DPP10 complex (abbreviated as the Kv4 complex)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…The drugs that can increase A-type K v currents reverse the pain phenotype [58]. On the contrary, reduced expression of the K v 4 channels and knockdown of any component of the K v 4 channel complex in primary neurons induce mechanical hypersensitivity, a major symptom of neuropathic pain [60,61]. Oxaliplatin, a chemotherapy drug, increases nociceptive neuron excitability to result in neuropathic pain in orofacial and other regions in patients, and the down-regulation of K v 4.3 channels and I A currents may be an underlying mechanism of oxalipaltin-induced orofacial neuropatic pain [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs that can increase A-type K v currents reverse the pain phenotype [58]. On the contrary, reduced expression of the K v 4 channels and knockdown of any component of the K v 4 channel complex in primary neurons induce mechanical hypersensitivity, a major symptom of neuropathic pain [60,61]. Oxaliplatin, a chemotherapy drug, increases nociceptive neuron excitability to result in neuropathic pain in orofacial and other regions in patients, and the down-regulation of K v 4.3 channels and I A currents may be an underlying mechanism of oxalipaltin-induced orofacial neuropatic pain [62].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in our present study, HpTx3 used in several pain models showed potent analgesic activity, suggesting that the analgesic effect of HpTx3 overwhelmed the hyperalgesia it caused. This result may be explained at least partially by the fact that in the pain models the level of K v 4 channels is usually decreased [56,61,64,65]. Till now, only one model showed that the expression of K v 4 channels was increased following injury [58].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal nerve ligation downregulated all three modulatory subunits, and their knockdown by intrathecal injection of a gene-specific antisense oligodeoxynucleotides evoked mechanical hypersensitivity. Rescue of the downregulated subunits by injection of appropriate cDNA constructs attenuated injuryinduced hypersensitivity (Kuo et al, 2017). These findings imply that targeting of regulatory subunits rather than pore-forming subunits of K + channels may lead the way to new therapeutic approaches.…”
mentioning
confidence: 90%
“…When external Ca 2+ is decreased, as during repetitive synaptic activity in the molecular layer of the cerebellum, the availability of stellate cell I SA is decreased to maintain inhibitory charge transfer to Purkinje neurons [92]. It will be interesting to see whether a comparable Kv4/KChIP/Cav nanodomain signaling also exists in other neurons, as suspected recently in the case of Kv4/KChIP/DPP complexes in nociceptive DRG neurons [93], or in cardiomyocytes. Notably, in cardiomyocytes KChIP2 may form a complex with Cav1.2 [68,69], maybe in combination with Kv4 channels.…”
Section: Acute Modulation Of the Kv4/kchip Channel Complex By Cytoplamentioning
confidence: 99%